Effect of ethanol treatment on morphological and technical properties of corn starch - Nguyen , Dang My Duyen; Nguyen , Quang Duy; Ly , Ngoc Bin (Journal of Technical Education Science, 2021)
Solvent exchange is considered an effective method that changes the physicochemical properties of starch, especially the absorption. Ethanol concentration is one of the important influencing factors to form porous pores from the surface to inside starch granules. In this study, the effect of ethanol concentration on technical properties of starch treated by solvents were investigated. The ratio of ethanol/water was prepared at 1/9, 3/7, 5/5, 7/3 and 10/0 (w/w), respectively. Corn starch was treated by solvent at 8% concentration. Morphology, oil and water holding capacity, solubility, swelling power, viscosity, and transmittance were studied to elucidate the effect of the ethanol concentration on the morphological and technical properties of corn starch treated by solvent. As a result, starch treated by solvent with different concentrations tended to form wrinkles and pore from the surface to the inside of the starch granules during ethanol immersion. Therefore, the oil and water holding capacity, solubility, swelling and viscosity of the solvent-treated starch samples increase as the concentration of ethanol increases. Otherwise, the transmittance of starch glues tends to decrease when the ethanol concentration increases.